Thermal infrared imaging of crop canopies for the remote diagnosis and quantification of plant responses to water stress in the field - Jones, Hamlyn G.; Serraj, Rachid; Loveys, Brian R.; Xiong, Lizhong; Wheaton, Ashley; Price, Adam H. (Commonwealth Scientific and Industrial Research Organisation, 2009)
Thermal imaging using infrared (IR) is now an established technology for the study of stomatal responses and for phenotyping plants for differences in stomatal behaviour. This paper outlines the potential applications of IR sensing in drought phenotyping, with particular emphasis on a description of the problems with extrapolation of the technique from the study of single leaves in controlled environments to the study of plant canopies is field plots, with examples taken from studies on grapevine (Vitis vinifera L.) and rice (Oryza sativa L.). Particular problems include the sensitivity of leaf temperature (and potentially the temperature of reference surfaces) to both temporal and spatial variation in absorbed radiation, with leaf temperature varying by as much as 15°C between full sun and deep shade. Examples of application of the approach to phenotyping in the field and the steps in data analysis are outlined, demonstrating that clear genotypic variation may be detected despite substantial variation in soil moisture status or incident radiation by the use of appropriate normalisation techniques.